AVALIAÇÃO ECONÔMICA E SOCIAL DE SISTEMAS DESCENTRALIZADOS DE ESGOTAMENTO SANITÁRIO - Jessica Vieira (2024)
Decentralized sewage treatment systems emerge as a solution to the search for universal basic sanitation. There is a diversity of decentralized wastewater treatment technologies available and capable of complying with release and/or reuse standards, when existing, and providing adequate services and benefits to the environment. However, choosing the most sustainable sewage alternative is a challenge. Social Life Cycle Assessment (ACV-S) and Life Cycle Cost Analysis (ACCV) are tools that can assist in decision-making regarding the most appropriate option for a set of treatment technologies for a given scenario. In this context, the present work comparatively evaluated, based on ACCV and ACV-S, nine scenarios with different configurations of decentralized treatment systems for single-family homes in peri-urban areas in Brazil. The nine scenarios evaluated represented different wastewater management practices, with direct discharge into the ground, disposal in rudimentary septic tanks, septic tanks and sinks, and in the sanitary sewage network. Technologies with source separation for recovery of water, nutrients and organic matter were also considered, such as the evapotranspiration tank (TEvap), for water from the toilet (dark water) and dry compostable toilet (feces), wetlands built for gray water and storage tank for yellow water (urine). A group of economic indicators was listed: construction cost (CAPEX), operation and maintenance cost (OPEX), total cost (TC) and net present value (NPV) and a group of social indicators: worker health and safety; labor; user health and safety; monetization; safe and healthy living conditions and economic development, divided into three stakeholders (workers, user and community). In the analysis of the social and economic impacts of the scenarios proposed through ACV-S and ACCV, the scenarios with the best performance in economic and social sustainability were the scenario with the EvaTAC configuration for gray water treatment and subsequent reuse and TEvap for the treatment of dark water, ranking first in both dimensions. Increased mainly by the reuse of gray water, compared to the scenario that has the same treatment system, but when gray water is not reused. Scenarios with a rudimentary septic tank achieved low performance in the social dimension and intermediate in the economic dimension, due to the small amount of material used in implementation and operation. The results of applying the methodology contribute to reflection on scenarios and decentralized sewage technologies that can be used in peri-urban areas in Brazil from an economic and social perspective, improving decision-making.